Efeitos da turbidez e complexidade do habitat no consumo e seletividade de tamanho das presas de Cichla kelberi (Kullander & Ferreira, 2006) - Menezes, Carlos Walker Fernandes (Universidade Federal Rural do Semi-Árido, 2016)
Alien species are causing various environmental impact on aquatic ecosystems throughout the world. As an example, alien fish introductions piscivorous habit have been associated with dramatic reductions in local diversity of native fish assemblages. To predict these impacts is necessary to understand environmental factors related to predation and selectivity of alien piscivorous fish, and some factors that may limit the invasive potential and the establishment of these non-native species due to reduction in the capture of prey, such as turbidity and complexity habitat as the presence of weeds for shelter. Thus, this study seeks to understand the Cichla kelberi species that has evaluated experimentally in a completely randomized design. The experiment was conducted in aquaculture center UFERSA, in plastic tanks containing approximately 500L of water, each with the presence of only predator, which was subjected to environments where the turbidity had 3 different levels (0, 60 and 120 NTU); 2 of macrophytes (presence or absence) and the selectivity of prey was evaluated by Chesson index, is offering 2- different prey sizes (the smallest with 2.87 ± 0.25 cm and the largest with 3.91 ± 0, 11 cm). The results of this study revealed that high levels of turbidity (120 NTU) consumption of prey has been reduced significantly; the presence of aquatic weeds did not affect the predator consumption and there was a preference for smaller prey of Oreochromis niloticus. In conclusion, this study showed behavioral information about the alien C. kelberi and factors that may limit their predation and providing empirical support for greater understanding of the species. Combined, these results support the hypothesis of the study and suggest that the impact of risk is reduced predation on aquatic ecosystems high turbidity and the presence of larger prey
Keywords: Predador; Tucunaré; Piscívoro; Espécies exóticas; Ecossistemas aquáticos; Predator; Tucunaré; Piscivorous; Exotic species; Aquatic ecosystems; CIENCIAS BIOLOGICAS::ECOLOGIA